Flight is the key to postprandial blood glucose balance in the fruit bats Eonycteris spelaea and Cynopterus sphinx - Peng, Xingwen (John Wiley and Sons Inc., 2017)

(untitled) (Ecol Evol)
Excessive sugar consumption could lead to high blood glucose levels that are harmful to mammalian health and life. Despite consuming large amounts of sugar‐rich food, fruit bats have a longer lifespan, raising the question of how these bats overcome potential hyperglycemia. We investigated the change of blood glucose level in nectar‐feeding bats (Eonycteris spelaea) and fruit‐eating bats (Cynopterus sphinx) via adjusting their sugar intake and time of flight. We found that the maximum blood glucose level of C. sphinx was higher than 24 mmol/L that is considered to be pathological in other mammals. After C. sphinx bats spent approximately 75% of their time to fly, their blood glucose levels dropped markedly, and the blood glucose of E. spelaea fell to the fast levels after they spent 70% time of fly. Thus, the level of blood glucose elevated with the quantity of sugar intake but declined with the time of flight. Our results indicate that high‐intensive flight is a key regulator for blood glucose homeostasis during foraging. High‐intensive flight may confer benefits to the fruit bats in foraging success and behavioral interactions and increases the efficiency of pollen and seed disposal mediated by bats.